ANALISIS CERPEN “KETIKA AKU DAN KAMU MENJADI KITA” MENGGUNAKAN PENDEKATAN OBJEKTIF - Azka Hanifa Sabila; Mega Nurhayati (Populer: Jurnal Penelitian Mahasiswa, 2022)
This research is to analyze the intrinsic elements in the short story “Ketika Aku dan Kamu Menjadi Kita” using an objective approach. The research method that I use in this analysis uses a qualitative descriptive method, which is a thorough and in-depth research. This short story is highly recommended to be read by all people because there is an educational element in the short story, and there are many messages and impressions in the short story. This plot is very understandable because it doesn't make the reader dizzy.